Enhancing policy dialogue on S&T for development in ACP countries - Greenidge, Carl B. (Technical Centre for Agricultural and Rural Cooperation, 2004)
The widely publicized revolution in technology, particularly in the areas of information communications and bio-technology, has rekindled interest in the potential of Science and Technology (S&T) to raise the rate of economic and social development and transformation of low income states. So far, the most dramatic evidence of this revolution is to be found primarily in the developed states and the most visible consequences for the low income states has been their accentuated marginalization